Rivers in prehistory : edited by Andrea Vianello. - Vianello, Andrea, 1975- (Archaeopress Publishing Ltd, 2015)
From antiquity onwards people have opted to live near rivers and major watercourses. Both freshwater and navigable routes provide the obvious reasons for settling near a river, but there are also many drawbacks, such as flooding. This volume explores rivers as facilitators of movement through landscapes, and it investigates the reasons for living near a river, as well as the role of the river in the human landscape. Ultimately, it focuses on the delicate relationship between humans and their environment, looking at the origins to help understand the present.